HAEMOPHAGOCYTIC LYMPHOHISTIOCYTOSIS AS A COMPLICATION OF VIRAL INFECTION IN A CHILD- CASE REPORT - Marianna Chmiel; Artur Tumiński; Gabriela Kapłon; Weronika Perczyńska; Julia Szczotka; Gabriela Szpila; Aleksandra Sokół; Anna Kamieniak; Karolina Glajcar; Remigiusz Flakus; Żaneta Kania; Dominika Gieroba (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and objective: Haemophagocytic lymphohistiocytosis (HLH) is a rare, life-threatening hyperinflammatory syndrome that may follow viral infections. We present a case of a 12-month-old boy who developed disseminated intravascular coagulation (DIC) and fulfilled HLH diagnostic criteria following influenza A virus infection. Extensive diagnostics excluded a genetic cause. Treatment based on the HLH-2018 protocol led to full recovery. This case emphasizes the importance of considering HLH in infants with severe systemic inflammation and coagulopathy, even in the absence of EBV infection. Early recognition and appropriate therapy are essential to improve outcomes. Results. This case report describes a 12-month-old boy with haemophagocytic lymphohistiocytosis (HLH) and disseminated intravascular coagulation (DIC) following influenza A infection. Despite negative genetic testing, the patient met HLH diagnostic criteria. Treatment per HLH-2018 protocol was successful. The case underscores the importance of early recognition of HLH in viral infections beyond Epstein-Barr virus.